I2‐Catalyzed/Mediated C−S and C−I Bond Formation: Solvent‐ and Metal‐Free Approach for the Synthesis of β‐Keto Sulfones and Branched Sulfones. Issue 8 (13th April 2023) - Tyagi, Aparna; Taneja, Neha; Khan, Jabir; Kumar Hazra, Chinmoy
Abstract: Herein, we report a solvent‐ and transition‐metal‐free, iodine‐catalyzed formation of C−S (sulfone) bonds for the synthesis of β ‐keto sulfones using readily accessible methyl ketones and sulfonyl hydrazides. This study also features the α ‐functionalization of β ‐keto sulfones to synthesize β ‐keto thiosulfones and α ‐iodo‐ β‐ keto sulfones via iodine‐catalyzed carbon‐sulfide (C−S) bond formation under solvent‐free conditions and iodine‐mediated C−I bond formation under aqueous conditions, respectively. The analytical studies and control experiments allow insights into a free‐radical coupling strategy. Overall, the presented protocol is operationally simple and scalable, has a broad range of functional group tolerance, and provides access to three functionalized organic scaffolds. Abstract :